Longitudinal Study Investigating the Relationship between Disease Activity and Psychological Status of Patients with Behçet's Disease. (18th May 2020) - Zulfiqar, Mehwaish H.; Shamdas, Mohith; Bashir, Abida; Douglas, Sarah; Murray, Philip I.
ABSTRACT: Purpose: To compare longitudinal changes in disease activity with quality of life and psychological status in patients with Behçet's disease (BD). Methods: Patients attending a National Centre of Excellence for BD over a two-year period had disease activity including clinician and patient perception of disease documented and completed a number of validated quality of life and psychological questionnaires. Some representative case-studies were examined in detail. Results: 102 patients were included. Disease activity weakly correlated with quality of life and psychological health. Clinician and patient perceptions strongly correlated with each other. Case-study analyses showed diverse, and sometimes incongruous, responses between, and in, individual patients. Conclusion: Changes in disease activity account for only a small proportion of changes in psychological status with intra-individual variation playing a large role. There is a complex relationship between psychological status and disease activity that cannot be explained by changes in disease activity alone.